2013
DOI: 10.3109/01612840.2013.771234
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the Development of Metabolic Syndrome in People with Psychotic Disorders—Difficult, but Possible: Experiences of Staff Working in Psychosis Outpatient Care in Sweden

Abstract: The aim of this study was to explore mental health staffs' experiences of assisting people with psychotic disorders to implement lifestyle changes in an effort to prevent metabolic syndrome. Qualitative interviews were conducted with 12 health care professionals working in psychosis outpatient care in Sweden. Data were analysed using a qualitative content analysis. The results illustrate that implementation of lifestyle changes among people with psychotic disorders was experienced as difficult, but possible. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…The main enabling factors to support participation in physical activity among individuals with severe mental illness have been shown to be the support of the mental health staff and organization and structure of the care organization (Hodgson et al, 2011). Master’s level mental health nurses need to have the skills to communicate lifestyle issues in such a way that it is adjusted to the person’s cognitive ability and the talent to supervise other professional groups to provide an empathic and seriously committed community-based social support (Bergqvist, Karlsson, & Fodemo et al, 2013). Master’s level mental health nurses need to be able to cooperate with health care providers, health agencies and the public in order to support the achievement of a healthy lifestyle, and support the individual with mental illness to enjoy increased social integration (Wärdig, Bachrach-Lindström, & Foldemo et al, 2013),…”
Section: Skillsmentioning
confidence: 99%
“…The main enabling factors to support participation in physical activity among individuals with severe mental illness have been shown to be the support of the mental health staff and organization and structure of the care organization (Hodgson et al, 2011). Master’s level mental health nurses need to have the skills to communicate lifestyle issues in such a way that it is adjusted to the person’s cognitive ability and the talent to supervise other professional groups to provide an empathic and seriously committed community-based social support (Bergqvist, Karlsson, & Fodemo et al, 2013). Master’s level mental health nurses need to be able to cooperate with health care providers, health agencies and the public in order to support the achievement of a healthy lifestyle, and support the individual with mental illness to enjoy increased social integration (Wärdig, Bachrach-Lindström, & Foldemo et al, 2013),…”
Section: Skillsmentioning
confidence: 99%
“…Even with most people with mental disorders knowing the importance of a healthy lifestyle, there were difficulties to change habits, because these patients had to implement these modifications and deal with and accept the psychotic symptoms. 8 Thus, the study identified that negative symptoms and cognitive alterations were the main obstacles to implement lifestyle changes in this population. Studies 8,9,18 with people with schizophrenia, an important psychotic disorder in the mental health field, confirm their low level of PA. 18 Healthy adults took, on average, between 7,000 and 13,000 steps in the first day of study, whereas the participants with that mental disorder took, on average, between 2,384 to 4,399 steps in the same time interval.…”
Section: Sedentary and Healthy Lifestylesmentioning
confidence: 99%
“…Other studies 8,13,16,17 stressed the importance of preventing metabolic syndrome in patients with mental disorders and active psychotic symptoms who take antipsychotic medications, because they have an increased risk of cardiometabolic comorbidities, including metabolic conditions such as obesity, insulin resistance, hypertension and diabetes. 16 These comorbid conditions can shorten life expectancy of people with a severe mental disorder 20% more than in people with no mental disease.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%
See 2 more Smart Citations